Impact of Cost Reduction Strategies on Purchasing and Procurement in Mozambique - Cossa, Abelina (Global Journal of Purchasing and Procurement Management, 2023)
Purpose: The study sought to analyze the impact of cost reduction strategies on purchasing and procurement in Mozambique. Methodology: The research was conducted entirely on computers. Secondary data, or data that doesn't require actual observation in the field, are the focus of desk research. Because it requires little more than an executive's time, telephone rates, and directories, desk research is generally seen as a low-cost strategy in comparison to field research. As a result, the research used data that had already been collected and reported. This secondary data was readily available via the internet's digital library and scholarly articles. Findings: The results show that cost reduction strategies are effective ways of reducing costs associated with purchasing and procurement. Cost reduction strategies enables companies to reduce costs associated with materials, services, and labor, as well as reduce overhead costs. Additionally, strategic partnerships and the use of technology also help companies reduce costs and optimize their purchasing and procurement process. Overall, cost reduction strategies can be an effective way of reducing costs and improving efficiency. Unique Contribution to Theory, Practice and Policy: Future research in the field of purchasing and procurement may be grounded in the competitive advantage theory and the supply chain theory. Policymakers, researchers and academics from all across the world will all stand to gain from this study's findings. Executives in charge of national purchasing and procurement initiatives will also use the study's findings to boost the cost reduction strategies performance across the board. The research suggests that the purchasing and procurement sector should implement cost reduction policies to boost the effectiveness of their primary operations and activities.